34.0k views
1 vote
Make a conjecture of what the x-intercepts of the function
f(x) = (2x - 1)(x + 3) will be.

User Francena
by
4.6k points

1 Answer

3 votes

Answer:

x=-3,x1/2

Explanation:

f(x)=(2x-1)(x+3)

TI find x intercept/zero substitute

f(x)=0

0=(2x-1)x(x+3)

swap the sides of the equation

(2x-1)x(x+3)=0

when the product of factors equals 0,at least one factor is zero

2x-1=0

x+3=0

solve the equation for x

x=1/2

x+3=0

solve the equation of x

x=-3

The equation has two solution

x=-3

x=1/2

User Andreas Vogl
by
5.9k points